1980
DOI: 10.1093/ajcn/33.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lipid peroxidation in liver microsomes of zinc-deficient rats

Abstract: The clinical association of decreased serum and hepatic zinc in patients with cirrhosis of the liver presumably arising from excess ethanol ingestion prompted a study of the activities of zinc and alcohol in experimental animals. The purpose of this study was to determine the effect of zinc deficiency upon lipid peroxidation in the liver. The effect of ethanol and zinc deficiency on lipid peroxidation was also evaluated. Rats were used in the experimental design, one group received a control diet, and one was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(30 citation statements)
references
References 35 publications
2
26
0
2
Order By: Relevance
“…However, our results showed that GPx and GSH were unaffected by both zinc deficiency and zinc overdose, which was consistent with the findings of Buzadžić et al [32] who observed that Zn supplementation had no effect on liver GPx activity in contrast to the control group . In the present study, after subjecting the rats to a zinc deficiency the hepatic MDA and H 2 O 2 content increased, CuZn SOD as well as CAT activities were inhibited in comparison with the control group, which was mostly in agreement with the findings of other researchers [7,33] . However, Buzadžić et al [32] and Pathak et al [34] found that Zn supplementation had no effect on liver CAT activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results showed that GPx and GSH were unaffected by both zinc deficiency and zinc overdose, which was consistent with the findings of Buzadžić et al [32] who observed that Zn supplementation had no effect on liver GPx activity in contrast to the control group . In the present study, after subjecting the rats to a zinc deficiency the hepatic MDA and H 2 O 2 content increased, CuZn SOD as well as CAT activities were inhibited in comparison with the control group, which was mostly in agreement with the findings of other researchers [7,33] . However, Buzadžić et al [32] and Pathak et al [34] found that Zn supplementation had no effect on liver CAT activity.…”
Section: Discussionsupporting
confidence: 93%
“…The mechanism by which zinc deficiency induced lipid peroxidation could be explained on the basis of the following evidence. First, zinc deficiency was found to induce an increase in microsomal phospholipids with the resultant high level of unsaturated fatty acids vulnerable for lipid peroxidation [33] . Second, zinc deficiency was shown to increase NADPH and cytochrome P450-dependent production of carboncentered free radicals in rat liver microsomes [35] .…”
Section: Discussionmentioning
confidence: 99%
“…These functions become apparent during zinc deficiency, with markedly increased levels of lipid peroxidation in plasma membranes as well as in mitochondrial and microsomal membranes. This leads, for example, to an increased fragility of erythrocyte membranes and an impaired homeostasis of platelets (Sullivan et al, 1980;Bettger and O'Dell, 1981;Bray and Bettger, 1990;Oteiza et al, 1995).…”
Section: The Role Of the Essential Trace Element Zinc In Metabolismmentioning
confidence: 99%
“…A decline in immune function in elderly can also be the consequence of an accumulation of activated oxygen free radicals and decreased activity of antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) (Sullivan et al, 1980). Zinc plays an important role in the antioxidant defense system and zinc deficiency has been associated with increased reactive oxygen-induced damage in various tissues (Kraus et al, 1997).…”
Section: Introductionmentioning
confidence: 99%